FRB 121102: Drastic changes in the burst polarization contrasts with the stability of the persistent emission. Issue 4 (24th February 2022) - Plavin, A; Paragi, Z; Marcote, B; Keimpema, A; Hessels, J W T; Nimmo, K; Vedantham, H K; Spitler, L G
ABSTRACT: We study milliarcsecond-scale properties of the persistent radio counterpart to FRB 121102 and investigate the spectro-polarimetric properties of a bright burst. For the former, we use European VLBI Network (EVN) observations in 2017 at 1.7 and 4.8 GHz. For the latter, we reanalyse the 1.7-GHz data from the 100-m Effelseberg telescope taken in 2016. These observations predate other polarimetric studies of FRB 121102, and yield the highest burst Faraday rotation measure (RM) to date, RM = 1.27 · 10 5 rad m −2, consistent with the decreasing RM trend. The fractional polarization of the burst emission is 15 per cent at 1.7 GHz. This can be reconciled with the high-fractional polarization at higher frequencies if the Faraday width of the burst environment is 150 rad m −2 – a bare 0.1 per cent of the total Faraday rotation. The width may originate from minor non-uniformities in the Faraday screen, or from effects in the emitting region itself. The upper limit on the persistent source size is 1 pc, barely consistent with a young supernova (SN) scenario. The flux variability limit of 10 per cent is not in favour of the young SN scenario, and challenges other interpretations as well. The fractional polarization of the faint persistent source is constrained at 25 per cent at 4.8 GHz ruling out a common origin with the highly polarized individual bursts.